Socialization of the Utilization of Narrow Land for Medicine Plants in an Effort to Increase Family Resilience and Adaptation During the Covid-19 Pandemic and Financial Management - Adia Adi Prabowo; Eko Yulianto (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
The Abdimas activity is aimed at PKK women in Pelem Hamlet, Baturetno, Banguntapan, Bantul who are generally affected by the Covid-19 pandemic. The existence of this ABDIMAS activity is expected to foster enthusiasm and awareness to increase family resilience and adapt to conditions caused by the Covid-19 pandemic, among others with narrow land use for medicinal plants and financial management. Abdimas activities are carried out through lectures and discussions, so that PKK Pelem Hamlet women can increase their awareness and ability to increase the resilience of their respective families from the impact of the COVID-19 pandemic and contribute to improving the economy of the people of Pelem Hamlet, Baturetno, Banguntapan, Bantul.